Comparing Brain Functional Activities in Patients With Blepharospasm and Dry Eye Disease Measured With Resting-State fMRI - Feng, Changqiang; Jiang, Wenyan; Xiao, Yousheng; Liu, Yang; Pang, Lulu; Liang, Meilan; Tang, Jingqun; Lu, Yulin; Wei, Jing; Li, Wenmei; Lei, Yiwu; Guo, Wenbin; et al. (Frontiers in Neurology, 2021)
Background: Blepharospasm (BSP) and dry eye disease (DED) are clinically common diseases characterized by an increased blinking rate. A sustained eyelid muscle activity may alter the cortical sensorimotor concordance and lead to secondary functional changes. This study aimed to explore the central mechanism of BSP by assessing brain functional differences between the two groups and comparing them with healthy controls. Methods: In this study, 25 patients with BSP, 22 patients with DED, and 23 healthy controls underwent resting-state functional magnetic resonance imaging (fMRI) scan. The amplitude of low-frequency fluctuations (ALFF) was applied to analyze the imaging data. Results: Analysis of covariance (ANCOVA) revealed widespread differences in ALFF across the three groups. In comparison with healthy controls, patients with BSP showed abnormal ALFF in the sensorimotor integration related-brain regions, including the bilateral supplementary motor area (SMA), left cerebellar Crus I, left fusiform gyrus, bilateral superior medial prefrontal cortex (MPFC), and right superior frontal gyrus (SFG). In comparison with patients with DED, patients with BSP exhibited a significantly increased ALFF in the left cerebellar Crus I and left SMA. ALFF in the left fusiform gyrus/cerebellar Crus I was positively correlated with symptomatic severity of BSP. Conclusions: Our results reveal that the distinctive changes in the brain function in patients with BSP are different from those in patients with DED and healthy controls. The results further emphasize the primary role of sensorimotor integration in the pathophysiology of BSP.